Temporal trend, spatial clustering of risk and social vulnerability of the prevalence of falls among the elderly in an area of Northeastern Brazil (2008-2015): an ecological study (Research, Society and Development, 2021)
Objective: to analyze a temporal trend, the spatial clusters of risk and association with social vulnerability in the prevalence of falls among the elderly in the state of Sergipe, Northeastern Brazil. Methodology: Ecological, exploratory and analytical study carried out in the state of Sergipe, Northeastern Brazil. Data were collected from the National Disease Notification System in Brazil, the Brazilian Institute of Geography and Statistics and the United Nations Development Program. A temporal and spatial analysis of the prevalence of falls among the elderly and the association with social vulnerability indicators was conducted. Results: In the period from 2008 to 2015, 273 cases of falls were reported among elderly people in the state of Sergipe. The trend in the analyzed period was 15.6%, decreasing in the period from 2008 to 2013 and increasing in 2013 to 2015. The spatial analysis identified a cluster of risk in the western region of the state. The indicators that are associated with the prevalence of falls related to income, education, aging and poverty. Conclusion: Spatial and temporal techniques defined as risk areas for falls among the elderly, as well as the identification of the associated social vulnerability factors.